Dietary Behaviours, Impulsivity and Food Involvement: Identification of Three Consumer Segments - Sarmugam, Rani (Nutrients, 2015)
This study aims to (1) identify consumer segments based on consumers’ impulsivity and level of food involvement, and (2) examine the dietary behaviours of each consumer segment. An Internet-based cross-sectional survey was conducted among 530 respondents. The mean age of the participants was 49.2 ± 16.6 years, and 27% were tertiary educated. Two-stage cluster analysis revealed three distinct segments; “impulsive, involved” (33.4%), “rational, health conscious” (39.2%), and “uninvolved” (27.4%). The “impulsive, involved” segment was characterised by higher levels of impulsivity and food involvement (importance of food) compared to the other two segments. This segment also reported significantly more frequent consumption of fast foods, takeaways, convenience meals, salted snacks and use of ready-made sauces and mixes in cooking compared to the “rational, health conscious” consumers. They also reported higher frequency of preparing meals at home, cooking from scratch, using ready-made sauces and mixes in cooking and higher vegetable consumption compared to the “uninvolved” consumers. The findings show the need for customised approaches to the communication and promotion of healthy eating habits.